Exploring autistic traits in parents of autistic children: a pilot study on the broader autism phenotype - Antonio Narzisi; Elena Maria Busuoli; Maddalena Fabbri-Destro; Martina Pinzino; Sara Calderoni; Sara Calderoni; Raffaella Tancredi; Michael Vincent Lombardo; Gabriele Masi (Frontiers in Psychiatry)
BackgroundBiological parents of autistic children often exhibit characteristics associated with the broader autism phenotype (BAP), a subclinical expression of autism-related traits. While BAP traits are known to be prevalent among first-degree relatives of autistic individuals, the relationship between parental traits and children’s characteristics remains under-explored.ObjectivesThis pilot study examines the presence and extent of BAP traits in an Italian sample of both biological mothers and fathers of autistic children, exploring also the correlations between parental BAP traits and children's autistic traits.MethodsSeventy-six autistic children (ages 4-11) and their biological parents were recruited for the study. Parental and child traits were evaluated using the Autism Quotient (AQ) and the Autism Diagnostic Observation Schedule-Second Edition (ADOS-2).ResultsOf the recruited sample of parents, 29% fell within the BAP, with 12% of fathers and 17% of mothers meeting the criteria. A significant difference was found in AQ scores between fathers and mothers, with fathers scoring higher on average. Fathers' AQ scores were significantly correlated with their children's AQ scores, while no significant correlation was observed between mothers' AQ scores and children's scores. Additionally, children's AQ scores correlated significantly with all Vineland Adaptive Behavior Scale (VABS) subscales but not with ADOS scores.ConclusionsThis study highlights the significance of parental BAP traits in relation to autism characteristics in children. The findings suggest that paternal BAP traits, in particular, may have a stronger association with child characteristics. Understanding these associations may contribute to refining psycho-educational strategies tailored to the specific traits of parents, ultimately enhancing intervention approaches.